Victoria Falls curio sector analysis: insights through the lens of a dollarized economy - Zhou, Zibanai (Africa Journals, 2021)
This study analyses the state of the informal curio sector in Victoria Falls in the obtaining multicurrency trading dispensation. The study sought to address a lacuna in the curio trading literature in the context of Zimbabwe`s re-calibrated economic environment. The study envisaged to broaden the private and government`s comprehension of curio trading and resultantly help policy shifts and the public narrative of curio business as a significant entrepreneurial activity in need of support. In-depth interviews and focus group discussion of 200 participants were used to gather the data. A thematic approach was used for data analysis. Results revealed that the curio business in Victoria Falls is at its lowest ebb due to a dwindling clientele base, and pittance curio prices amongst a host of other attendant factors. Findings further established that incessant harassment from municipal police coupled with an opaque allocation system of market stalls that are far flung from tourist hotspots riled traders. A dormant local market, poor signage of curio stalls and exorbitant monthly rentals levied by council were bemoaned as Achilles Heels of the informal curio business. The study recommends curio traders to form trade associations and social co-operatives to bolster their bargaining powers and access cheap financial resources. To ameliorate the rampant entrepreneurial skill deficiency amongst the rank and file of curio traders, they should enrol for night and weekend schools to upgrade their skills. The study lacks external validity hence it is necessary to replicate it at national level using a different methodological approach.